New generic concepts for orphaned lineages formerly treated as part of the genus Ocyptamus Macquart, 1834 (Diptera, Syrphidae) - Miranda, Gil Felipe Gonçalves; Skevington, Jeffrey H.; Marshall, Stephen A. (Zootaxa, 2020)
The large syrphid genus Ocyptamus Macquart has been subject to scrutiny in recent years, resulting in a more narrowly defined monophyletic Ocyptamus sensu stricto. Some of the species excluded from this narrower concept of the genus are in evolutionary lineages for which generic names are available, but other species are in lineages for which generic names do not exist. The current paper presents five new genera to correct this: Fragosa gen. nov. (former Ocyptamus stenogaster group), Hypocritanus gen. nov. (former Ocyptamus fascipennis group), Maiana gen. nov. (former Ocyptamus callidus group), Nuntianus gen. nov. (former Ocyptamus lepidus group) and Victoriana gen. nov. (former Ocyptamus melanorrhinus group). In addition to the new combinations related to these new genera, Argentinomyia aenea (Williston) comb. nov., Hybobathus pola (Curran) comb. nov., H. subchalybeus (Walker) comb. nov., H. wilhelmina (Doesburg) comb. nov., and Leucopodella nasuta (Williston) comb. nov. are moved out of Ocyptamus. Ocyptamus isthmus Thompson is a jun. syn. of Callostigma panamensis Curran stat. rev. Relevant morphological characters and their taxonomic and evolutionary implications are discussed.